Montelukast Efficacy for Improvement of Adult Acute Phase Mild-Moderate Asthma Attack: A Clinical Trial Study - Motamed, Hassan; Verki, Mohammadreza M.; Barzegari, Hassan; Shariat, Siamak; Hesam, Saeed (Current Respiratory Medicine Reviews, 2020)
Background: Asthma, an inflammatory disease of the respiratory tract, is one of the most frequent causes of referral to emergency departments. The aim of this study is to evaluate the efficacy of montelukast as a member of LTRAs for the improvement of pulmonary function and clinical symptoms of patients with asthma. Methods: The study was conducted on 80 patients with acute mild- moderate asthma, divided randomly into two groups of 40 subjects. A double-blind clinical trial was conducted on asthmatic patients who encounter an acute phase asthma attack. The experimental group received two montelukast 5 mg chewable tablets at arrival, accompanied by standard mild-moderate asthma treatment consisting of oxygen and nebulization with albuterol 2.5 mg and ipratropium bromide 0.5 mg in 3 doses for 60 minutes. The control group received standard mild-moderate asthma treatment plus placebo chewable tablets at the beginning without any leukotriene inhibitors. Pulmonary function tests, hemodynamic variables and Borg Dyspnea Scale were evaluated and analyzed at 0, 30, 60, 90 and 150 minutes in both case and control groups. Results: No significant differences were observed between the case and the control group in terms of PEFR and FEV1 measurements during the study at different time points [P > 0.05]. There were no significant differences in terms of hemodynamic variables [blood pressure, pulse and respiration rate, pressure of oxygen in arterial blood] and Borg Dyspnea Scale in both groups as well. Conclusion: The study findings showed that the montelukast administration in mild-moderate acute asthma attack setting had no significant impact on pulmonary function tests and clinical symptoms of the studied patients rather than standard asthma treatment.
Keywords: leukotriene inhibitors